Politisasi Masjid Perspektif Hukum Pidana Islam - Makmun, Moh. (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
This paper aimed at investigating the criminal aspects of Islamic criminal law about politicization of mosque and their legal sanctions. This paper furthermore can contribute to policy maker for preventing the spread of this phenomenon and give an understanding of the legal sanctions from the politicization of mosque in perspective islamic criminal law. The research concludes that politicization of the mosque is in the category of jarîmah ta'zîr. The criminal aspect in the politicization of mosque perspective of Islamic criminal law are: 1). Violating religious orders about obligation to obey the leader. 2). violating the Prophet Muhammad's prohibition. 3). violates the basic principles of Islam which calls for the spread of peace on earth, prohibition to doing damage on earth, and because it causes many disobedience and obedience, such as division and speech of hatred. The legal sanctions for the actor of politicization of mosque are at the discretion of the judge The legal sanctions for the actor of politicization of mosque are at the discretion of the judge with taking into account the size of the madharat or losses incurred based on maqashid shariah and flexibility of jarîmah ta‘zîr.